ANALISIS PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. Cen Kurir Indonesia, Jakarta) - Bagaskara, Bagus Ikhsan; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to analyze the influence of work motivation, work discipline and job satisfaction on the employee performance of PT. Cen Kurir Indonesia, Jakarta. Fluctuating phenomenon of employee performance level at PT. Cen Kurir Indonesia, Jakarta indicates that employee performance has not been maximized. This study uses three independent variables of work motivation, work discipline and job satisfaction.Data collection methods used in this study is the spread of questionnaires using non- proportional stratified sampling method, the sample used in this study are employees of PT. Cen Kurir Indonesia, Jakarta as many as 73 respondents. This research uses data analysis methods such as validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, F test and hypothesis test.The results of this study indicate that the variables of work motivation, work discipline and job satisfaction positively affect the performance of employees of PT. Cen Kurir Indonesia, Jakarta. These variables have an effect of 56.1% on employee performance. The rest of 43.9% influenced by other variables outside of this study.